ANALIS POTENSI AIR TANAH DI KECAMATAN LEMBAH GUMANTI - fitri, fitri yani; U, Iswandi (DEPARTEMEN GEOGRAFI FIS UNP, 2025)
The demand for clean water in the Gumanti Valley continues to increase as the population grows. On the other hand, the distribution of groundwater continues to decrease due to the reduction of infiltration areas. Groundwater potential mapping is conducted to determine the groundwater potential in an area, this is the first step in identifying and locating local water sources. Remote sensing data and geographic information systems were used to identify groundwater potential in this study. To determine groundwater potential, an overlay was conducted using the Weighted Overlay method. Based on the evaluation results, groundwater potential is classified into three classes: low, medium and high. Areas with low groundwater potential are spread over 341 ha, medium groundwater potential areas are 19,265 ha and high groundwater potential areas are 5,065 ha. The map results obtained can be used as a reference in finding suitable locations for exploitation of groundwater resources.